Substitutions at Loop Regions of TMUV E Protein Domain III Differentially Impair Viral Entry and Assembly - Hu, Tao; Wu, Zhen; Wu, Shaoxiong; Wang, Mingshu; Jia, Renyong; Zhu, Dekang; Liu, Mafeng; Zhao, Xinxin; Yang, Qiao; Wu, Ying; Zhang, Shaqiu; Huang, Juan; et al. (Frontiers in Microbiology, 2021)
Flavivirus envelope protein (E) plays an important role in cellular infection, especially in virulence and antigenicity. E domain III of Tembusu virus is highly conserved among flaviviruses and contains four loop regions. However, the functions of the loop regions of TMUV E domain III in the viral life cycle have not yet been discovered. In this study, using a reverse genetics system, we performed site-directed mutagenesis on loops Ⅰ, Ⅱ, Ⅲ, and Ⅳ of TMUV E domain Ⅲ. Mutant 6 (S388A.G389A.K390A) showed better proliferation than the wild-type virus, while mutants 1-5 exhibited decreased in vitro infectivity, as determined by IFA. Based on TMUV replicon system, the mutations exhibited no apparent effect on TMUV RNA replication. Subcellular fractionation assays and packaging system assays indicated that mutations in loops II-Ⅳ (T332A, T332S, S365A. S366A. T367A and S388A. G389A. K390A, respectively) disrupted virion assembly. Moreover, loops I-IV played an important role in virus binding and entry, while mutant 6 (S388A.G389A.K390A) exhibited robust activity in virus entry. Taken together, our findings indicated the critical role of the loop regions in TMUV E domain III in the virus entry and assembly process.